THE LEGAL NATURE OF MIXED MARRIAGE DIVORCE UNDER INDONESIAN LAW: JURISDICTIONAL AUTHORITY OF THE RELIGIOUS COURT IN TRANSNATIONAL MARITAL DISPUTES - Mochammad Rohman Antoni (YURIS: Journal of Court and Justice, 2025)
This study examines the legal nature of mixed marriages and divorce within the Indonesian legal system, focusing on the authority of Religious Courts in adjudicating such cases. Using a normative juridical and qualitative approach, the research analyzes statutory provisions, doctrinal interpretations, and judicial practices through a case study of Decision Number 406/Pdt.G/2020/PA.Dps issued by the Denpasar Religious Court. The findings indicate that mixed marriage divorces involving Indonesian citizens and foreign nationals fall under the jurisdiction of Religious Courts when one spouse is an Indonesian Muslim. The court’s decision aligns with Law Number 1 of 1974 on Marriage, Government Regulation Number 9 of 1975, Law Number 12 of 2006 on Citizenship, and the Compilation of Islamic Law (KHI). The study concludes that the Religious Court applies the principles of lex loci celebrationis and lex fori to ensure that Indonesian law governs the dissolution of mixed marriages. This legal approach ensures justice, legal certainty, and state protection for Indonesian citizens engaged in transnational marital relationships.